Bibliometric review of the scientific production of oral health in Latin America and The Caribbean during COVID-19 pandemic - Jaime Alfredo Ortega Romero; Pablo Alejandro Millones Gomez; Ricardo Wagner Cabezas Nieves; Elsa Inche Arce; Franco Alfonso Mejia verastegui; Jackeline Lizet Meza Orihuela; Ana Cecilia Pascual Serna (Editorial Ciencias Médicas, 2023)
Introduction: The bibliometric analysis of the scientific production in health allows detailing the interest of authors, institutions, organizations and journals that contributed to a better understanding of the natural history of SARS-CoV-2, in relation to oral health. Objective: To characterize the bibliometrics of scientific production in oral health, related to COVID-19 pandemic in Latin America and the Caribbean. Methods: One hundred forty-three articles were analyzed from Scopus database, which were published in 2020 and 2021. This study considered the annual scientific production, the ten authors, institutions and organizations with the greatest publication activity, the ten main journals involved in article publications on the subject, as well as the most cited bibliometric terms. Results: In 2020, seventy three articles on the subject were published, which decreased by 5.47% for 2021. The institutions most involved in publications were from the United States, Peru, and Brazil. The most active author was Machado R.A. The journal Pesquisa Brasileira em Odontopediatria e Clínica Integrada was the most cited with 8.47%, the most cited article was "Impacts of coronavirus COVID-19 on Dentistry and salivary potential" with 119 citations and the most used descriptors were "the humans", "pandemic" and "dentistry". Conclusion: The largest scientific production of cited articles, authors with the highest number of citations, and highly-published journals on oral health in Latin America and the Caribbean is in Brazil. The institution with the greatest support activity for the publication of scientific articles and the most used descriptors "pandemic", "human" and "2019 coronavirus disease" are in the United States.